Tumor DNA from tumor in situ fluid was used to track evolution of glioma under first-line treatment - Yu, Jinliang; Gao, Yushuai; Zhang, Jiubing; Wang, Dayang; Deng, Kaiyuan; Wu, Shuang; Zhang, Ziyue; Yan, Zhaoyue; Liu, Guanzheng; Dong, Liujian; Li, Tao; Feng, Shubin; et al. (Frontiers in Oncology, 2025)
IntroductionFew studies have tracked the genetic evolution of glioma recurrence in patients after surgery. We conducted a systematic review through an innovative sampling method, which made post-operative follow-up possible. Tumor DNA from Tumor in situ fluid (TISF) was used to trace the genetic landscape of gliomas at different stages of recurrence and evolution.MethodsWe recruited 60 patients with WHOII-III gliomas diagnosed more than 6 years ago. We performed whole exome sequencing (WES) of primary tumor tissues and paired TISF to identify somatic mutations by personalized, tumor-informative TISF-DNA testing. TISF and recurrent tumor tissues were collected at simultaneous and 2-3 month routine visits. Patients were followed up for clinical recurrence.ResultsIn gliomas dominated by genomic alleles with low frequency (variant allele fraction, VAF < 1%), imaging residues had higher VAF (p = 0.016), and patients with postoperative recurrence also had higher VAF (p < 0.0001). Under the pressure of treatment, multiple mutations gradually increased with tumor evolution, and dominant high-frequency mutation gradually appeared. Samples of relapsed TISF contained much more abundant clonal mutations. Sequencing of relapsed tumor tissue and relapsed TISF samples showed high consistency in mutation detection and estimation of allele frequency (p < 0.0001, VAF correlation, R2 = 0.8737). In patients under continuous surveillance, the tumors at different stages showed heterogeneity. We determined that TISF may detect elevated Tumor DNA VAF prior to positive imaging findings and effectively identify patients with pseudoprogression.DiscussionTISF-DNA showed high consistency with tumor tissue, showing the genetic landscape of glioma at different stages after surgery. It can even be used to identify false progression during glioma treatment. Even in the absence of imaging findings, glioma DNA recurrence should arouse clinical concern and induce new research.